2011
DOI: 10.1016/j.jval.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Measures to Enhance the Value of Observational Surveys in Rare Diseases: The Fabry Outcome Survey (FOS)

Abstract: We conclude that the measures introduced in 2005 significantly improved the value of the information in the registry, which has contributed greatly to our understanding of patients' real-world experience with enzyme replacement therapy for Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Disease registries, especially for rare diseases, are becoming valuable resources for obtaining and reporting information [Basso et al, 2004; Moss and Schwartz, 2005; Wilkinson et al, 2010; Byrne et al, 2011; Clarke et al, 2011]. Centralized longitudinal and natural history data as well as the potential to link specific clinical data with DNA or tissue specimens are becoming useful tools for evaluating pathophysiology, genotype–phenotype correlation, genetic modifiers, and potential therapies [Basso et al, 2004; Moss and Schwartz, 2005; Wilkinson et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease registries, especially for rare diseases, are becoming valuable resources for obtaining and reporting information [Basso et al, 2004; Moss and Schwartz, 2005; Wilkinson et al, 2010; Byrne et al, 2011; Clarke et al, 2011]. Centralized longitudinal and natural history data as well as the potential to link specific clinical data with DNA or tissue specimens are becoming useful tools for evaluating pathophysiology, genotype–phenotype correlation, genetic modifiers, and potential therapies [Basso et al, 2004; Moss and Schwartz, 2005; Wilkinson et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Centralized longitudinal and natural history data as well as the potential to link specific clinical data with DNA or tissue specimens are becoming useful tools for evaluating pathophysiology, genotype–phenotype correlation, genetic modifiers, and potential therapies [Basso et al, 2004; Moss and Schwartz, 2005; Wilkinson et al, 2010]. Registries are also recognized for the potential to evaluate outcomes and efficacies of certain therapies [Basso et al, 2004; Clarke et al, 2011] and are increasingly being used by industry for this purpose in rare diseases [Byrne et al, 2011; Clarke et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that 2 years of GH replacement therapy reduced the risk of cardiovascular events by 50%, and that male sex and high total cholesterol were potential predictors of this response [30]. Similarly, the Fabry Outcome Survey (FOS), established in 2001 as an industry-sponsored, physician-directed registry of patients with Fabry disease (FD), a rare lysosomal storage disorder, has made an important contribution to the understanding of both the disease and the patients’ real-world experience of enzyme replacement therapy [31]. In other rare diseases, registries have proven valuable for revealing shortcomings of current treatment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The use of healthcare claims databases to assess at UNIV OF GUELPH on February 3, 2015 tah.sagepub.com Downloaded from treatment cost and outcomes has proved valuable in this regard, and several strategies are now available to optimize datasets obtained from such studies [Motheral and Fairman, 1997]. Furthermore, patient registries allow the natural history and response to treatment of rare diseases to be studied in greater depth than would otherwise be achievable [Clarke et al 2011]. Overall, the value of observational studies lies in their focus on everyday clinical practice, reflecting the differences between consecutive patients that make treatment decisions so interesting and, in some cases, so challenging.…”
Section: Observational Studies: Complementary To Randomized Controllementioning
confidence: 99%